Supercritical fluid extraction of Eichhornia crassipes - Silva, Rui Pedro Fonseca Ferreira da (2014)
The aim of this thesis was to evaluate the potential of Eichhorina crassipes harvested from Pateira de Fermentelos, Águeda, as a source of phytosterols, namely stigmasterol, by Soxhlet and supercritical fluid extraction. Supercritical extractions were used in this thesis as an alternative to conventional techniques that use organic solvents, allowing the assessment of both extractions in terms of concentration, yield and selectivity for stigmasterol. In both cases chemical evaluation was carried out using different techniques: GCMS, total phenol content and antioxidant activity. With this intent, an experimental work plan was established. First, the biomass was harvested and divided in its different morphological parts, roots, stalks, leaves and flowers. Secondly, soxhlet extractions with dichloromethane were performed and the extracts analyzed by GC-MS. This step revealed a strong stigmasterol concentration in stalks and leaves (15.0% and 13.5%; mg/100mgextract) and a total yield value of 1.12, 2.65, 3.30 and 4.45 wt.% respectively. Thirdly, solid liquid extractions were performed and total phenolic and antioxidant activity were assessed, revealing that leaves possessed higher phenolic content and antioxidant activity than all other morphological parts. Finally, supercritical fluid extractions (SFE) were performed. These were divided in two stages. In the preliminary stage, a mixture of all parts where submitted to extraction revealing a lower overall extraction yield but higher stigmasterol concentration (31% mg/100mgextract). The second phase of SFE was performed in order to obtain the overall extraction curves (OEC). These were performed with a biomass mixture that revealed a higher stigmasterol content, namely stalks and leaves. These extractions demonstrated that temperature had little effect on the total yield, that the optimal time of extraction was of one hour and the maximum stigmasterol concentration was achieved after two hours of extraction. Regarding the modeling of the extraction curves, internal diffusion revealed to be the dominant mass transfer mechanism. In sum, these results show that supercritical extraction of E. crassipes biomass can become a promising extraction technology, generating rich stigmasterol extracts, opening a possible window for its commercial implementation.